Comparison of Blue and White Lamp Light with Sunlight for Daylight‐Mediated, 5‐ALA Photodynamic Therapy, in vivo. (16th May 2018) - Marra, Kayla; LaRochelle, Ethan P.; Chapman, M. Shane; Hoopes, P. Jack; Lukovits, Karina; Maytin, Edward V.; Hasan, Tayyaba; Pogue, Brian W.
Abstract: Daylight‐mediated photodynamic therapy (d‐PDT) as a treatment for actinic keratosis (AK) is an increasingly common technique due to a significant reduction in pain, leading to better patient tolerability. While past studies have looked at different light sources and delivery methods, this study strives to provide equivalent PpIX‐weighted light doses with the hypothesis that artificial light sources could be equally as effective as natural sunlight if their PpIX‐weighted fluences were equalized. Normal mouse skin was used as the model to compare blue LED light, metal halide white light and natural sunlight, with minimal incubation time between topical ALA application and the onset of light delivery. A total PpIX‐weighted fluence of 20 Jeff cm −2 was delivered over 2 h, and the efficacy of response was quantified using three acute bioassays for PDT damage: PpIX photobleaching, Stat3 crosslinking and quantitative histopathology. These bioassays indicated blue light was slightly inferior to both sunlight and white light, but that the latter two were not significantly different. The results suggest that metal halide white light could be a reasonable alternative to daylight PDT, which should allow a more controlled treatment that is independent of weather and yet should have similar response rates with limited pain during treatment. Abstract : In this study, three light sources were directly compared for daylight‐mediated photodynamic therapy efficacy. Two artificial light sources, a blue LED and a ceramic metal halide white light, were compared to natural sunlight. Each source's spectral irradiance was normalized to the absorption spectrum of the photosensitizer, protoporphyrin IX (PpIX), to deliver a precisely matched total light dose. Acute bioassays including immunoblot and quantitative histopathology, pictured above, reveal that all three light sources were effective mediators, although blue light was found to be slightly inferior.